Clinical Legal Education in Indonesia Objectives and Advantages - Rodiyah, Rodiyah (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) in Indonesia embodies a transformative approach to legal education, with distinct objectives and advantages. CLE's primary goals include enhancing practical skills, bridging the gap between theory and practice, and fostering a sense of social responsibility. Through real-world engagement, students develop crucial skills like legal research, client counseling, and courtroom advocacy. The objective of promoting community engagement aligns with Indonesia's commitment to social justice, encouraging legal practitioners to address the needs of marginalized communities. Additionally, CLE contributes to ethical and professional development, guiding students through real ethical dilemmas to establish a robust ethical foundation. The interdisciplinary nature of CLE promotes collaboration with professionals from various fields, providing students with a holistic understanding of legal issues and their broader societal implications. The advantages of CLE in Indonesia are manifold. Graduates with CLE experience exhibit enhanced legal competence, making them highly sought after by employers. This practical skill set not only increases employability but also positions graduates to excel in a rapidly evolving legal landscape. The networking opportunities facilitated by CLE contribute to the building of professional relationships crucial for career advancement and mentorship. Moreover, CLE students become agents of legal reform, actively contributing to improvements in the legal system and its responsiveness to societal needs. In essence, CLE in Indonesia stands as a catalyst for producing socially conscious, skilled legal professionals equipped to address the challenges of the legal profession.